Vitamin D deficiency, fatigue, and persistent cough as independent predictors of depressive symptoms in sarcoidosis patients - Gvozdenovic Branislav S.; Mihailovic-Vucinic Violeta; Vukovic Mira; Omcikus Maja; Cvejic Jelena; Belic Slobodan; Jankovic Jelena; Đurđevic Natasa; Stjepanovic Mihailo (Journal of Medical Biochemistry)
Background: Depressive symptoms are frequent in sarcoidosis. We assessed the impact of sarcoidosis symptoms, pulmonary function, fatigue, radiographic findings, comorbidities, treatment, and serum levels of 25-hydroxyvitamin D (25(OH)D) on depressive symptoms in sarcoidosis patients. Methods: In a cross-sectional study, we measured depressive symptoms using the Center for Epidemiologic Studies - Depression Scale (CES-D) and fatigue using the Fatigue Assessment Scale (FAS). Presence of depressive symptoms was defined with CES-D scores ≥16 and ≥20, respectively. Fatigue was defined as having an FAS score of ≥22. Results: A total of 400 patients were included in the study. CES-D score ≥16 had 128 patients, while CES-D score ≥20 had 86 patients. In a multivariate binomial logistic regression model, the following independent predictors of CES-D score ≥16 were identified: female gender (odds ratio, OR 1.983), chronic sarcoidosis (OR 2.311), serum levels of 25(OH)D ≤20 ng/mL (OR 2.326), persistent dry cough (OR 2.173), FAS Scores ≥22 (OR 9.243), and chest X-ray stage 3 (8.851). Five variables were independent predictors of CES-D score ≥20: diplopia (OR 4.411), FEV1 <80% predicted associated with FVC <80% predicted (OR 2.311), serum levels of 25(OH)D ≤20 ng/mL (OR 2.278), persistent dry cough (OR 3.001), and FAS Scores ≥22 (OR 7.611). Conclusions: Measuring the contribution of low serum 25-hydroxyvitamin D and the impact of persistent dry cough on depressive symptoms in patients with sarcoidosis may be crucial in deciding whether to use vitamin D3 alone or with antitussive therapy before the psychiatric diagnosis of depression with antidepressant therapy initiation.